Constructing three-dimensional (3D) nanoflower-like Cu2-xSe-MoSe2 heterojunction as an excellent long-life and high-rate anode for half/full Na-ion batteries. (10th November 2022) - Li, Shengkai; Zhang, Shangshang; Zhang, Haiyan; Liu, Zhenjiang; Yang, Changsheng; Wang, Yan; Wan, Baoshan; Wen, Daofeng
Abstract: Transition metal selenides with good economy and high theoretical capacity are the most attractive anode materials for sodium-ion batteries (SIBs). However, the severe volume expansion during sodiumization/desodiumization still hinders the wide application of this material. Nano heterojunction materials with lattice distortion not only improve the thermal stability and reaction kinetics, but also the contact area between active materials and electrolyte is increased to enhance the cycle and rate. Herein, three-dimensional (3D) nanoflower-like Cu2-x Se-MoSe2 (CMSe) heterojunction is successfully prepared through a facile co-precipitation and hydrothermal method, the prepared 3D CMSe heterojunction anode for SIBs exhibits a high reversible capacity of 549.1 mAh g − 1 over 100 cycles at 0.2 A g − 1, superior rate capability of 350.59 mAh g − 1 at 20 A g − 1, and excellent cycling stability (335 mAh g − 1 at 2.0 A g − 1 over 4000 loops). The excellent sodium storage performance can be ascribed to its 3D nanoheterojunction structural features, which can enhance the contact area with electrolyte, buffer volume changes, improve its structural stability during cycling. In addition, the deep reaction mechanism is sufficiently explored by means of ex situ XRD and HRTEM. When further coupled with Na3 V2 (PO4 )3 cathode in sodium-ion full cells, it also delivers excellent electrochemical performance. Therefore, 3D CMSe heterojunction is promising anode materials for SIBs.